Determinants of AI Non-Fungible Tokens Gaming and Blockchain based Digital Marketing: A Revolution of Metaverse in Asia Pacific Region - Siddique, Hafiz Muhammad Adeel; Yaqub, Rana Muhammad Shahid; Akram, Hafiz Muhammad Zeeshan; Khurshid, Rashid (Pakistan Journal of Humanities and Social Sciences, 2023)
The adoption of Non-Fungible Tokens (NFTs) has witnessed a significant surge in recent years. NFTs are digital assets that operate on blockchain technology and are traded using cryptocurrencies such as Ethereum, Tezos, Solana, among others. However, there is limited knowledge regarding the economics of NFTs and people's perspectives and experiences with them. Therefore, the purpose of this research is to present diverse understandings of NFT gaming and digital marketing, analyze the benefits and drawbacks of NFTs, and explore their potential in the metaverse. This study utilizes a qualitative investigation approach involving nine respondents from the NFT, blockchain, and gaming communities. The research employs case study and descriptive analysis methods. The conclusion drawn from this study recommends the utilization of NFTs and expects readers to find this research beneficial. NFTs represent digital assets that are uniquely identifiable and traded using blockchain technology and cryptocurrencies. Despite their popularity and increasing trading prices, there is a lack of comprehensive understanding regarding the economics of NFTs, as well as people's perspectives and experiences with them. This research aims to address this gap by providing diverse insights into NFT gaming and digital marketing, exploring the benefits and drawbacks of NFTs, and investigating their potential in the metaverse. The study employs a qualitative investigation methodology and involves nine participants from the NFT, blockchain, and gaming communities. The research utilizes case study and descriptive analysis methods to gather and analyze data. The study examines the impressions and experiences of individuals engaged in crypto games. The results indicate that most players dedicate 2 to 6 hours per day to playing crypto games. Moreover, it is found that the time required recovering one's investment in these games ranges from 1 to 90 days. The findings also reveal that players are concerned about the presence of potential economic instability in a volatile market. Additionally, issues such as value manipulation, privacy, security, and trust related to the design and utilization of NFTs are highlighted. Understanding the cryptocurrency market entails understanding the motivations of individuals who engage in paid games, as their interests are crucial for any government initiatives aimed at generating revenue. The study recommends that players explore the NFT Pakistan game.